'Sitting alone in the staffroom contemplating my future': communities of practice, legitimate peripheral participation and student teachers' experiences of problematic school placements as guests. Issue 4 (1st October 2016) - Johnston, David H.
Abstract : A recent Review of Teacher Education in Scotland reports that 23% of respondents ( n = 2381) encountered variable or very poor school placement experiences. This paper uses Lave and Wenger's ideas concerning Communities of Practice (1998) and Legitimate Peripheral Participation (1991) as analytical tools with which to understand the nature and impact of student teachers' problematic experiences of school placement. A total of 14 Professional Graduate Diploma in Education students on a one-year Secondary English course were followed through the practice elements of their Initial Teacher Education programme and data were constructed from learning logs and semi-structured interviews. Analysis provided a nuanced account of the student teachers' difficulties in attaining member status as Legitimate Peripheral Participants in communities of practising teachers, with the concepts 'joint enterprise', 'mutual engagement' and 'shared repertoire' being found to be useful in explaining these difficulties. Limitations in the theoretical framework were also discovered and these are highlighted and developed in the paper.